2016
DOI: 10.3390/ijerph13050453
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast and Other Meal Consumption in Adolescents from Southern Poland

Abstract: The aim of the study was to evaluate the frequency of breakfast and other meal consumption by adolescents and to assess the relationship between the first and the last meal consumption and sex, body mass index (BMI), and middle school and high school students’ education level. The study was conducted in 2013–2014 among 3009 students (1658 girls and 1351 boys) from middle s and high schools in Krakow and Silesia (Poland). The data was obtained from questionnaires that were analyzed with a logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
26
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
8
26
1
6
Order By: Relevance
“…Over 4% of adolescents in this study skipped breakfast the entire week before they were surveyed, which is consistent with previous findings that 4% of children and adolescents habitually skip breakfast (Berkey et al 2003; Resnicow 1991) but lower than other findings that indicated over 12% of urban adolescents skipped breakfast (Lawman et al 2014; Ostachowska-Gasior et al 2016). In a study that utilized a 4-day eating behavior survey and a 24-hour dietary recall to examine breakfast eating behaviors in a similar, but younger, sample of low-income African American children in New Jersey, Sampson et al (1995) found that 22%–26% of children did not eat anything for breakfast.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Over 4% of adolescents in this study skipped breakfast the entire week before they were surveyed, which is consistent with previous findings that 4% of children and adolescents habitually skip breakfast (Berkey et al 2003; Resnicow 1991) but lower than other findings that indicated over 12% of urban adolescents skipped breakfast (Lawman et al 2014; Ostachowska-Gasior et al 2016). In a study that utilized a 4-day eating behavior survey and a 24-hour dietary recall to examine breakfast eating behaviors in a similar, but younger, sample of low-income African American children in New Jersey, Sampson et al (1995) found that 22%–26% of children did not eat anything for breakfast.…”
Section: Discussionsupporting
confidence: 92%
“…In a study that utilized a 4-day eating behavior survey and a 24-hour dietary recall to examine breakfast eating behaviors in a similar, but younger, sample of low-income African American children in New Jersey, Sampson et al (1995) found that 22%–26% of children did not eat anything for breakfast. The data from this study showed that girls consumed breakfast less frequently than boys and that younger adolescents consumed breakfast more frequently than older adolescents, with some significant findings between various age–sex groups, which is consistent with previous research that indicated that breakfast skipping is more common among girls and older adolescents (Lawman et al 2014; Ostachowska-Gasior et al 2016; Rampersaud et al 2005). Therefore, trends in frequency of breakfast consumption among low-income, urban, predominantly African American adolescents observed in the present study are consistent with those seen on the national level.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A környezet által közvetített kockázati tényezők mellett a pszichoszociális hatások (önértékelési zavar, testi elégedetlenség, identitásproblémák) és a hormonális változások is jelentősek [31,35,36]. Ostachowska-Gasior és mtsai a lengyel serdülők körében végzett vizsgálataik alapján a reggeliző és nem reggeliző egyének testtömegindex-(BMI-) értékei között nem találtak szignifikáns különbséget, viszont a rendszertelen étke-zés, a nassolás, valamint a súlygyarapodás között jelentős összefüggést igazoltak [38]. Ebben a korszakban az ideálok szerepe nagy.…”
Section: Megbeszélésunclassified